Mongolia Public Financial Management Performance Report - World Bank (Washington, DC, 2015)
This public financial management performance report (PFM-PR) is the first assessment of Mongolia’s PFM system using the public expenditure and financial accountability (PEFA) framework. The report aims principally to establish an objective baseline measure of current PFM performance, highlighting areas of absolute and relative strength and weakness, thereby enabling a stock-taking of over a decade of PFM reforms in Mongolia and guiding the government in its reform priorities. The assessment covers PFM at the budgetary central government level. The PEFA is an evidence-based methodology that measures the performance of a country’s PFM system at a particular point in time using a set of standardized indicators. The assessment is done on six dimensions of an open and orderly PFM system identified by the framework, which are: credibility of the budget; comprehensiveness and transparency; policy-based budgeting; predictability and control in budget execution; accounting, recording, and reporting; and external scrutiny and audit. This PEFA assessment will complement the considerable work that has already taken place on public expenditure management, which includes regular economic updates, public investment reviews, procurement reviews, analytic work conducted and supported by the World Bank funded technical assistance projects, as well as technical assistance mission reports of the International Monetary Fund (IMF).